The Content and Specific Features of Reconstructing the Residential Houses of Various Configurations - Zakharov, Yu.I.; Sankov, P.M.; Trifonov, I.V.; Tkach, N.O.; Toshyna, L.O. (Science and Innovation, 2024)
Introduction. After the World War II in the countries of Western and Eastern Europe, as a result of war devastations and population growth, a housing crisis arose, because of which, in the 1950's, there was a boom in the construction of small cheap apartments. Problem Statement. Because of massive development, the issues of consumer quality of apartments, their comfort, durability, and energy efficiency was in the focus of public attention and, as early as in the early 1980's, these houses had not met the norms and technical requirements and required reconstruction works. In many European countries, this problem has been successfully solved, while in Ukraine it has been relevant so far. Purpose. To introduce unified design schemes for the reconstruction of the first series of mass houses on the territory of Ukraine by establishing the possibility of re-planning and rearrangement of apartments to improve the quality of residential facilities for future inhabitants. Materials and Methods. Analysis of events and publications on the status and possibilities of reconstruction of the first series mass houses. Results. The content and features of reconstruction of the first series mass residential houses (FSMRH) of the mentioned period are considered in view of their structure and configuration, taking into account the experience of the countries of Western and Eastern Europe. The document that is part of verification of the reconstruction strategy has been developed. It is divided into the two additional tests: 1) a test complement to the three thematic studies in Belgium, France, and Switzerland; 2) test of the prospects of interaction with stakeholders (investors, housing owners, and public administration). Conclusions. Structural systems and configurations for the reconstruction of the first mass series houses in Ukraine have been considered. The unified scheme of re-planning and rearrangement of the first mass series houses with different structural systems and configurations has been presented. The reconstruction of the first mass series houses for which resettl